EHT 1864, a small molecule inhibitor of Ras-related C3 botulinum toxin substrate 1 (Rac1), attenuates glucose-stimulated insulin secretion in pancreatic β-cells - Sidarala, Vaibhav (Cell Signal, 2015)
Glucose-stimulated insulin secretion (GSIS) in the pancreatic β-cells entails a variety of signaling mechanisms including activation of small GTP-binding proteins (G-proteins). Previous studies from our laboratory in human islets, rodent islets and clonal β-cells have demonstrated that G-proteins (e.g., Arf6, Cdc42 and Rac1) play novel roles in cytoskeletal remodeling, which is a critical step in the trafficking of insulin-laden secretory granules for fusion with plasma membrane and release of insulin. To further understand regulatory roles of Rac1 in GSIS, we utilized, herein, EHT 1864, a small molecule inhibitor, which attenuates Rac1 activation by retaining the G-protein in an inert/inactive state, thereby preventing activation of its downstream effector proteins. We demonstrate that EHT 1864 markedly attenuated GSIS in INS-1 832/13 cells. In addition, EHT 1864 significantly reduced glucose-induced activation and membrane targeting of Rac1 in INS-1 832/13 cells. This Rac1 inhibitor also suppressed glucose-induced activation of ERK1/2 and p53, but not Akt. Lastly, unlike the inhibitors of protein prenylation (simvastatin), EHT 1864 did not exert any significant effects on cell morphology (cell rounding) under the conditions it attenuated Rac1-sensitive signaling steps leading to GSIS. Based on these findings, we conclude that EHT 1864 specifically inhibits glucose-induced Rac1 activation and membrane association and associated downstream signaling events culminating in inhibition of GSIS.